Perancangan Mekanisme Partisipasi Komunitas dalam Program Kerja POKDARWIS di Kampung Bekelir - Rizkaa, Witha Shofani; Bonetha, Sylvia; Hartono, Yudo; Zulandari, Peni (Stupa, 2021)
This research was conducted from April to August 2019, focusing on Kelompok Sadar Wisata (POKDARWIS) in Kampung Bekelir, Tangerang. POKDARWIS is a form of organization which aims for the enhancement of local community’s role and authority as the subject of tourism development in a certain area. Increases in the community’s well-being, especially in the economic well-being, becomes the expected outcomes of every project made by POKDARWIS. Based on the research that was conducted using Soft System Methodology, researchers found that POKDARWIS in Kampung Bekelir had difficulties in creating its own project. Therefore, to make sure that POKDARWIS’ projects are suitable with the needs and the wants of the local comunity, they need to actively participate in the decision making process of POKDARWIS’ project. In order to achieve an active community participation, the local community needs to be included from the planning, implementation, to the evaluation of a project.